Fatigue as a key human factor in complex sociotechnical systems: Vessel Traffic Services - Fernando Crestelo Moreno; Fernando Crestelo Moreno; Verónica Soto-López; Deva Menéndez-Teleña; Joaquín Roca-González; Juan Suardíaz Muro; Cristina Roces; Mercedes Paíno; Imma Fernández; Luis Alfonso Díaz-Secades (Frontiers Media S.A., 2023)
BackgroundVessel Traffic Services (VTS) are considered a subsystem of people, whose mission is to improve the effectiveness and efficiency of maritime transport within the maritime system. VTS operate as a control system where Vessel Traffic Services Operators (VTSOs) must cope with a complex environment to make up for safe and efficient maritime transport, so it is essential to understand how these operators maintain control through adapting to the uncertain and dynamic environment of maritime traffic. This multidisciplinary study explores how human factors within this complex sociotechnical system, means VTS, play a role in maritime safety, specifically focusing on fatigue, which is considered a key variable for VTSOs' performance. In this context, the research has focused on the assessment of fatigue with psychological and operational instruments to highlight the importance of the human element in CSSs.ObjectiveTo study the intra and inter-individual differences in fatigue ratings and their relationships with other personal and environmental variables: mental workload, work shifts, reaction time, and hours of usual sleep.MethodsThe study was conducted in two of the 19 Spanish Maritime Rescue Coordination Centers (MRCCs) with a sample of 23 active VTSOs (82.14% of the staff). Both objective and standardized subjective measures were used to assess fatigue and associated sleepiness (Borg RPE, Nasa-TLX, Stanford Sleepiness Scale, and Self-Assessment Manikin Scale).ResultsA significant positive correlation between fatigue and mental workload was found, being more prevalent in the night shift, which shows a bigger variation in these variables. A significant difference was found in the increase in fatigue experienced throughout the shift depending on the hours of usual sleep, being smaller in the group of subjects reporting to sleep more.ConclusionThe human element is key to maritime safety related to Vessel Traffic Services, so it is of paramount importance to consider certain measures to counteract the negative effects of fatigue. A proper organization of duties on/off periods, assessment of work and rest schedules, and the implementation of fatigue management programs based on sleep education are recommended.